Which open infrastructures? - Aguillo, Isidro F. (Anuario ThinkEPI, 2023)
There is a strong movement for radical reform of the scientific evaluation processes in accordance with the principles of the open science initiative. To support the new system, one or several open platforms specifically designed for evaluation purposes is badly needed. A brief critical evaluation of some of the services currently used or available is carried out, and it is concluded that, although they provide important content that can be reused, the services alone are not enough nor completely suitable for rigorous, reliable and transparent evaluation. A proposal for a new tool is introduced with a brief analysis of its feasibility, along with a description of the needs and characteristics it must comply with.
Keywords: Open Science; Open infrastructures; Research evaluation; Academic databases; Metrics